Handbook of Antenna Technologies - Chen, Zhi Ning.; Liu, Duixian; Nakano, Hisamatsu; Qing, Xianming; Zwick, Thomas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The Handbook of Antenna Technologies aims to present the rapid development of antenna technologies, particularly in the past two decades, and also showcasing the newly developed technologies and the latest applications. The handbook will provide readers with the comprehensive updated reference information covering theory, modeling and optimization methods, design and measurement, new electromagnetic materials, and applications of antennas. The handbook will widely cover not only all key antenna design issues but also fundamentals, issues related to antennas (transmission, propagation, feeding structure, materials, fabrication, measurement, system, and unique design challenges in specific applications). This handbook will benefit the readers as a full and quick technical reference with a high-level historic review of technology, detailed technical descriptions and the latest practical applications. .
Theory -- Design -- Applications. .
Keywords: Telecommunication; Signal processing; Communications Engineering, Networks; Signal, Speech and Image Processing .; Microwaves, RF Engineering and Optical Communications